2007
DOI: 10.1562/0031-8655(2001)0730600potsop2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of the Sunscreen Octyl p-Dimethylaminobenzoate by UVA in Human Melanocytes but not in Keratinocytes¶

Abstract: Sunscreens penetrate human epidermis and modify the biology of proliferating cells. This study addressed the question whether the UV response of cultured human cells is affected by direct treatment with nontoxic levels of sunscreens. Cell survival following exposure to UVC or unfiltered UVB was not altered by preincubation with 25 g/mL of octyl p-dimethylaminobenzoate (o-PABA), 2-ethylhexyl p-methoxycinnamate (EHMC) or oxybenzone. However, UVA or UVB filtered to reproduce the solar UV spectrum penetrating to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Sunscreen concentration-human keratinocyte culture response curves were then defi ned using changes in cell morphology and proliferation (DNA synthesis using radiolabelled thymidine uptake studies) as evidence of sunscreens causing toxicity. Following 24 h of human epidermal exposure to sunscreens, detectable amounts of all sunscreens were present in the stratum corneum and viable epidermis, systemic absorption of sunscreens into man [3][4][5][6] or their adverse effects on isolated human cell cultures [7][8][9] . In addition, sunscreens have been associated with photoallergic reactions [10][11][12] , although the incidence in the exposed population is rare [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Sunscreen concentration-human keratinocyte culture response curves were then defi ned using changes in cell morphology and proliferation (DNA synthesis using radiolabelled thymidine uptake studies) as evidence of sunscreens causing toxicity. Following 24 h of human epidermal exposure to sunscreens, detectable amounts of all sunscreens were present in the stratum corneum and viable epidermis, systemic absorption of sunscreens into man [3][4][5][6] or their adverse effects on isolated human cell cultures [7][8][9] . In addition, sunscreens have been associated with photoallergic reactions [10][11][12] , although the incidence in the exposed population is rare [13] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ODP alone has strong absorption in the UVB range that leads to increased photoprotective effect against cell lethality in this range. However, it did not display any antimutagenic effect; contrariwise, ODP has been previously reported to cause photosensitization when associated to short‐wavelength UVA and long‐wavelength tail of UVB …”
Section: Resultsmentioning
confidence: 90%
“…PABA-ester has been reported to penetrate human epidermis and may selectively damage melanocytes in the skin. 160 There is controversy about mutagenicity of PABA and its derivatives; some studies stated that PABA is a weak mutagen, whereas others indicated that it is neither mutagenic nor photomutagenic. 161 In vitro and in vivo studies of photogenotoxicity and cytotoxicity of PABA have been reviewed.…”
Section: Controversies Concerning Sunscreensmentioning
confidence: 99%